Pengaruh Gaya Kepemimpinan Transformasional Dan Komunikasi Interpersonal Terhadap Kinerja Pegawai Dinas PU Bina Marga Propinsi Sumatera Selatan - Anton Trianto; Mahdi Hendrich; Marita Pratisila; Mustikawati (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2023)
This research aims to see the influence of transformational leadership style and interpersonal communication on employee performance at the Public Works Department of Highways, South Sumatra Province. The results show that partially/individually the transformational leadership style has a significant effect of 32.9% and interpersonal communication has a significant effect of 26.4% on the performance of employees of the South Sumatra Province Public Works Department of Highways. Simultaneously/together, transformational leadership style and interpersonal communication have a significant effect of 65.8% on the performance of employees of the South Sumatra Province Public Works Department of Highways. The application of a transformational leadership style is the factor that has the most dominant influence on the performance of employees of the Public Works Department of Highways, South Sumatra Province.